Use of locking compression plates for deformity correction of the forearm bones in children - Jochymek, Jiří; Škvařil, Jan; Starý, David; Gál, Petr; Plánka, Ladislav (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2009)
THE AIM OF THE STUDY: The aim of our study was to assess treatment results of angular deformities in distal radius by a system of the locking compression plates (LCP) at our clinic. METHODS: Our source data was collected prospectively from the records of patients where the locking compression plate was used for angulation correction of distal forearm between 2006 and 2007. The patients were divided by sex, the age range was defined and two groups were formed based on the initial diagnosis: the group of posttraumatic deformities (2 patients; 29 %) and the group of no traumatic deformities (3 patients with congenital shortening of ulna, valgus deformity and overgrowth of radius and 2 patients with exostoses multiplices with shortening of ulna and overgrowth of radius with ulnar angulation). The following parameters were set: radial articular angle and carpal slip prior to and after angulation correction, the healing period, the range of movement of the surrounding joints and occurrence of complications. RESULTS: We recorded only one case of delayed healing which was subsequently sustained by autospongioplastics and adjusted to normal. In the rest of the cases deformity correction occurred and the defined parameters were then corrected to normal. We observed no postoperative complications or permanent consequences. CONCLUSIONS: A two-year follow-up period monitoring treatment and therapeutic results of deformities in the forearm bones at our clinic, confirmed a minimal incidence of complications and a high percentage of successfully treated cases.
Keywords: Fracture Healing; Internal Fixators; Female; dítě; interní fixátory; hojení fraktur; ženské pohlaví; Adolescent; Ulna Fractures; fraktury vřetenní kosti; lidé; Ulna; radius; Radius; Bone Plates; kostní destičky; Male; fraktury ulny; vrozené deformity končetin; Child; mužské pohlaví; Limb Deformities, Congenital; mladiství; Radius Fractures; ulna; Humans